TOP MANAGEMENT EXPERTISE AND REAL PROFIT MANAGEMENT: MODERATING ROLES OF AUDIT COMMITTEES AND INDEPENDENT COMMISSIONERS - Odiatma, Fajar; Zarefar, Atika; Afriana Hanif, Rheny; Abdurrahman, Rezi; Multi Konvokesen Adiman, Raja (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2026)
This study examines the effects of independent board and audit committee expertise on Top Management Teams (TMT) and Real Earnings Management (REM) relationships.The sample in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2015 – 2024 with a total of 240 companies. Analysis of the research model using General Least Square (GLS). TMT financial and accounting skills are positively associated with REM. On the other hand, the financial and accounting expertise of the independent board and audit committee has a negative impact on the relationship between TMT and REM expertise. Other findings show consistent results for family firms and non-family firms. These findings are relevant and have implications for public policies related to good corporate governance (GCG), especially in countries with a two-tier system. The impact of the financial and accounting expertise of independent board and audit committee as a moderating variable in the relationship between TMT expertise and REM practices is still rare, especially in countries with two-tier systems. The results of this study show the importance of financial and accounting expertise from independent board and audit committees for effective control mechanisms that can ultimately reduce information asymmetry, especially information related to company profits.